2021
DOI: 10.1371/journal.pone.0244950
|View full text |Cite
|
Sign up to set email alerts
|

The significance of cytoplasmic antinuclear antibody patterns in autoimmune liver disease

Abstract: We aimed to determine the significance of cytoplasmic antinuclear antibody (ANA) patterns using computer-aided immunofluorescence microscopy in patients with autoimmune liver diseases (AILD). ANA staining pattern was identified by treating cultured human epithelial type 2 (HEp-2) cells with the sera of the patients. Medical records of patients with suspected AILD who had positive cytoplasmic ANA patterns between February 2017 and November 2019 were retrospectively reviewed for clinical, laboratory, and immunol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“…Patients with a reticular cytoplasmic staining showed a higher positive frequency for mitochondrial autoantibodies and a lower positive frequency for smooth muscle autoantibodies and nuclear ANA staining than people who exhibited the speckled cytoplasmic pattern. 69 Therefore, they concluded that positive cytoplasmic reticular staining patterns should be employed to manage autoimmune liver disease description in presumed clinical cases.…”
Section: Extension Of Autoantibody-based Diagnostics With Uncommon Au...mentioning
confidence: 99%
“…Patients with a reticular cytoplasmic staining showed a higher positive frequency for mitochondrial autoantibodies and a lower positive frequency for smooth muscle autoantibodies and nuclear ANA staining than people who exhibited the speckled cytoplasmic pattern. 69 Therefore, they concluded that positive cytoplasmic reticular staining patterns should be employed to manage autoimmune liver disease description in presumed clinical cases.…”
Section: Extension Of Autoantibody-based Diagnostics With Uncommon Au...mentioning
confidence: 99%
“…Autoimmune liver diseases are detectable using the peripheral homogeneous and filamentous subtypes of cytoplasmic fluorescence [18]. The mitochondrial subtype of cytoplasmic fluorescence is highly specific and indicative of autoimmune liver disease [19]. Fine speckled fluorescence has very low specificity and may indicate the presence of systemic rheumatic diseases, atopic dermatitis, psoriasis, or an oncological process [20].…”
Section: сучасна роль антинуклеарних антитіл у процесі ранньої діагно...mentioning
confidence: 99%
“…Antinuclear antibodies (ANA) are a general term for organ-specific autoantibodies that essentially use various cellular components of eukaryotic cells as target antigens, and the spectrum of specific antibodies against the multiple substances in the nucleus is regarded as ANA spectrum[ 1 , 2 ]. It is irreplaceable and essential for the clinical diagnosis, disease assessment, and efficacy evaluation of different autoimmune diseases[ 3 ]. The main techniques commonly used for ANA detection involve indirect fluorescent assay (IFA), enzyme-linked immune sorbent assay (ELISA), and LIA.…”
Section: Introductionmentioning
confidence: 99%